2020
DOI: 10.1111/aor.13675
|View full text |Cite
|
Sign up to set email alerts
|

Right atrial versus right ventricular HeartWare HVAD position in patients on biventricular HeartWare HVAD support: A systematic review

Abstract: In patients with biventricular heart failure or refractory right heart failure following HeartWare HVAD placement, off‐label placement of a right‐sided HeartWare HVAD has been described both in the right ventricular (RV) and right atrial (RA) positions. We sought to evaluate and compare the outcomes of right‐sided HeartWare HVAD using the RA versus RV approach. An electronic search was performed in the English literature to identify all reports of left‐ and right‐heart support with HeartWare HVAD. Of the 1,288… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Fourteen studies with a total of 399 CF-BiVAD recipients were reviewed. One study was a systematic review (16), and all others were observational studies. Three studies were registry reviews, one Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS), one European Registry of patients with Mechanically Assisted Circulatory Support (EUROMACS), and one of the United Network for Organ Sharing (UNOS) database.…”
Section: Quality Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen studies with a total of 399 CF-BiVAD recipients were reviewed. One study was a systematic review (16), and all others were observational studies. Three studies were registry reviews, one Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS), one European Registry of patients with Mechanically Assisted Circulatory Support (EUROMACS), and one of the United Network for Organ Sharing (UNOS) database.…”
Section: Quality Of Studiesmentioning
confidence: 99%
“…Although device numbers were not consistently reported, most studies delineated which devices were utilized on their participants (Table 3). Eleven of these studies (15,16,(23)(24)(25)(26)(27)(28)(29)(30)(31) utilized the HeartWare HVAD (Medtronic, Minnesota MN) whereas only three studies reported the use of the HeartMate 3 (Abbott, Chicago, IL) (27,32,33) (Figure 2). Timing of RVAD implantation as either concomitant with LVAD versus delayed was reported in most studies (12 of 14) and was predominantly implanted concomitantly (median 82%, IQR 62-84%).…”
Section: Devices Techniques and Configurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…BiVAD strategies have also utilized off-label placement of continuous flow LVADs in a right atrial or RV position. A systematic review of right-sided use of the HeartWare found that right atrial VAD placement results in a survival advantage compared to RV VAD placement (50). Overall, BiVAD support remains infrequent and is only utilized in approximately 5% of patients with MCS devices (35).…”
Section: Right Ventricular Assist Device (Rvad) Bivad and Total Artificial Heart (Tah)mentioning
confidence: 99%
“…6,16 In biventricular failure patients, low pump speed of the HVAD as RVAD is used typically 1900 RPM in order to produce low pressure output between 14 -23 mmHg and normal cardiac output between 4 -5 L/min. 9,10,17 While appropriate adjustments to HVAD's operating specifications have reported success supporting right heart failure and pediatric patients, it is potentially associated with a high rates of major adverse events; multisystem organ failure, neurological dysfunction, respiratory failure, pump thrombosis, infection, stroke, and major bleeding. 10,[18][19][20][21][22] This study was designed to evaluate the effect of HVAD on hemolysis, platelet activation and vWF degradation in adult systemic, pediatric systemic and adult pulmonary flow conditions.…”
Section: Introductionmentioning
confidence: 99%